An acyclic zincagermylene: rapid activation of dihydrogen at sub-ambient temperature. Issue 94 (14th November 2017) - Juckel, Martin M.; Hicks, Jamie; Jiang, Dandan; Zhao, Lili; Frenking, Gernot; Jones, Cameron
Abstract : The first zincagermylene (see picture) has been prepared and shown to have unprecedented reactivity for a germylene, with respect to the activation of dihydrogen; partially a result of its narrow HOMO–LUMO separation. Abstract : The first example of a stable zincagermylene, :Ge(TBoN)(ZnL*) (TBoN = N(SiMe3 )B(DipNCH)2 , Dip = C6 H3 Pr i 2 -2, 6; L* = –NC6 H2 [C(H)Ph2 ]2 Me-2, 6, 4(SiPr i 3 )) is prepared and shown to have unprecedented reactivity for a germylene, with respect to the activation of dihydrogen. Computational analyses point towards this being partially derived from the electron releasing nature of the amido–zinc fragment, which leads to a narrowing of the HOMO–LUMO gap in the compound.